Multidimensional Equality of Opportunity in the United States - Paul Hufe; Martyna Kobus; Andreas Peichl; Paul Schüle (Center for Economic Studies and ifo Institute (CESifo), 2022)
Are the United States still a land of opportunity? We provide new insights on this question by invoking a novel measurement approach that allows us to target the joint distribution of income and wealth. We show that inequality of opportunity has increased by 77% over the time period 1983-2016. Increases are driven by two distinct forces: (i) a less opportunity-egalitarian distribution of income until 2000, and (ii) a less opportunity-egalitarian distribution of wealth after the financial crisis in 2008. In sum, our findings suggest that the US have consistently moved further away from a level playing field in recent decades.
Keywords: D31; D63; J62; 330; fairness; intergenerational mobility; time trends; measurement